Anthropocentric way of naming of geographical objects in Ancient Greek - Чекарева, Євгенія Сергіївна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”)
The article represents an analysis of nouns-names of geographical objects in Ancient Greek formally and substantially connected with names of human body parts. The most impotent factor of such a group of lexemes formation is that all the system of spatial orientation is built on the base of biological and psychological nature of a man. The quantity of lexemes in each semantic group is also represented. The connection between specific features of the world picture typical for archaic may of cognition and their fixation in lexical system of Ancient Greek is also put in the article.